Investigation of DC glow discharge in CO₂ using optical emission spectroscopy - Lisovskiy, V.A.; Krol, H.H.; Dudin, S.V. (Вопросы атомной науки и техники, 2018)
The results of investigations of a glow discharge in carbon dioxide by the method of optical emission spectroscopy are presented. Processes in negative glow, positive column and anode glow are considered in detail. In the
negative glow, bright radiation lines of both atoms and molecules and their ions are observed: O, O⁺
, CO, O₂, CO⁺
and molecular continuum. In the positive column, a weak continuum and emission lines of CO₂, CO, and O₂ molecules are seen. The emission lines of CO molecules dominate in the anode glow against the background of the continuum, and also lines of molecular and atomic oxygen are visible. Axial intensity distributions of a number of lines
are presented for the entire discharge gap between the cathode and the anode. Наведені результати досліджень тліючого розряду у вуглекислому газі методом оптичної емісійної спектроскопії. Розглянуто докладно процеси в негативному світінні, позитивному стовпі і анодному світінні. У
негативному світінні спостерігаються яскраві лінії випромінювання як атомів, так і молекул і їх іонів: O, O⁺
,
СО, О₂, СО⁺
, та молекулярний континуум. У позитивному стовпі видно слабкий континуум і лінії випромінювання молекул CO₂, CO та O₂. В анодному світінні на фоні континууму домінують лінії випромінювання
молекул CO, а також видні лінії O₂ і атомарного кисню. Наведені осьові профілі інтенсивностей ряду ліній
для всього розрядного проміжку між катодом та анодом. Приведены результаты исследований тлеющего разряда в углекислом газе методом оптической эмиссионной спектроскопии. Рассмотрены подробно процессы в отрицательном свечении, положительном столбе и
анодном свечении. В отрицательном свечении наблюдаются яркие линии излучения как атомов, так и молекул и их ионов: O, O⁺
, СО, О₂, СО⁺
, и молекулярный континуум. В положительном столбе видны слабый
континуум и линии излучения молекул CO₂, CO и O₂. В анодном свечении на фоне континуума доминируют
линии излучения молекул CO, а также видны линии O₂ и атомарного кислорода. Представлены осевые профили интенсивностей ряда линий для всего разрядного промежутка между катодом и анодом